Study of physical characteristics of Indian handball players at different level of competition - Amandeep Sıngh; Vishaw Gaurav (Türk Spor ve Egzersiz Dergisi)
The purpose of the study was to compare the physical characteristics between Indian male handball players at different level of competition. The present study was conducted on a sample of forty eight(N=48), which includes twenty four each, male inter-school level (N1=24, mean ± SD: age 18.12 ± 0.80 years, height 176.83 ± 5.83cm, weight 69.04 ± 6.99 kg, BMI 22.07 ± 1.89) andinter-college level (N2=24, mean ± SD: age 20.54 ± 0.93 years, height 181.29 ± 3.44cm, weight 74.04 ± 3.89 kg, BMI 22.53 ± 1.30) handball players who participated in inter-school competitions of the schools affiliated to Punjab School Education Board and inter-college competitionsof Guru Nanak Dev University, Amritsar, Punjab, India respectively. All the participants were informed about the aim and methodology of the study and they volunteered to participate in this study. All the participants were assessed for height, weight and selected physical characteristics. The height of the subjects was measured with anthropometric rod to the nearest 0.5 cm. The weight of subjects was measured by using portable weighing machine to the nearest 0.5 kg. The vertical jump test was used to measure explosive power of the legs whereas speed was determined by 30 meters dash. Illinois agility test was used to measure agility and medicine ball put testwas used to determine the shoulder girdle strength. The independent samples t-test was applied to assess the differences between inter-school and inter-college level handball players.The level of significance was set at 0.05.The results of present study clearly indicated that inter-college level handball players had significantly greater power (p lt;0.05), speed (p lt;0.05), strength (p lt;0.05) and agility (p lt;0.05) than inter-school level male handball players. The inter-college level male handball players were also found taller and heavier as compared to inter-school level players.